Transnational Translation: Reflections on Translating from Judeo-Spanish and Spanglish - Attig, Remy (TTR)

(untitled) (Association canadienne de traductologie, 2019)
Judeo-Spanish and Spanglish are language varieties of minoritized communities at the geographic and cultural edges of the Spanish-speaking world. Literature is being published in both varieties as a way of carving out a space for the speakers of these varieties in societies (the US and Israel for the most part) that value linguistic homogeneity as a national unifying force. This paper grapples with two challenges that emerge when translating literature motivated by such political motivations into English: 1) translating hybridity and 2) orality. It then goes on to explore a few strategies that I have applied to some translations in an effort to address these challenges. The readers of American English translations have been taught to believe in nation-based categorizations of identity that, while they may be useful in many cases, do not accurately describe the “hybrid” contexts whence these source texts emerged. Similarly, orality is ever-present in language varieties that have been rarely written. Recognizing that a translation strategy for such literature must strive to respond to the cultural realities of both the source and target culture, this paper proposes two strategies that attempt to bring this hybridity and orality to an English reader.